"Anti-electrostatic" Halogen Bonding between Ions of Like Charge - Holthoff, Jana M.; Weiss, Robert; Rosokha, Sergiy; Huber, Stefan M. (Chemistry - A European Journal, 2021)
Halogen bonding occurs between molecules featuring Lewis acidic halogen substituents and Lewis bases. It is often rationalized as a predominantly electrostatic interaction and thus interactions between ions of like charge (e. g., of anionic halogen bond donors with halides) seem counter-intuitive. Herein, we provide an overview on such complexes. First, theoretical studies are described and their findings are compared. Next, experimental evidences are presented in the form of crystal structure database analyses, recent examples of strong "anti-electrostatic" halogen bonding in crystals, and the observation of such interactions also in solution. We then compare these complexes to select examples of "counter-intuitive" adducts formed by other interactions, like hydrogen bonding. Finally, we comment on key differences between charge-transfer and electrostatic polarization.
CRIS-Team WoS Importer:2021-10-08